Susceptibility of six varieties of rice to the infestation of rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae) - Khan, Humayun Reza; Halder, Polash Kanti (Dhaka University Journal of Biological Sciences, 2012)
The susceptibility of six varieties of rice, Oryza sativa, viz. Lata, Minicate, Nazersail, Parija, Kalijira and Kataribhog, to the infestation of the rice weevil, Sitophilus oryzae (L.), was studied on the basis of population build up under an ambient condition (28 ± 4ºC and 70 ± 4 % RH) of the laboratory. The mean weights of each grain of the above six rice varieties were 16.9, 16.1, 11.43, 13.87, 6.23 and 9.77 mg, respectively; mean lengths were 6.47, 6.56, 5.37, 5.38, 4.22 and 4.92 mm, respectively; mean widths were 2.45, 2.03, 2.05, 2.17, 1.6 and 1.9 mm, respectively; and moisture contents were 11.55, 10.75, 11.6, 12.71, 11.85, and 12.1 per cents, respectively. As far as the number of emerging adults is concerned, the weevil showed the highest number (695) in Nazersail on the 16th week, Lata (755) on the 18th week, Minicate (654) on the 16th week, Parija (482) on the 20th week, Kalijira (402) on the 20th week, and Kataribhog (456) on the 20th week. The mean numbers of the adult weevils in the above six varieties after 22 weeks of rearing were 425, 410, 351, 387, 357 and 400, respectively and was statistically significant at 5% level. The degree of susceptibility of the rice varieties to the rice weevils from the highest to lowest susceptibility was ? Lata > Nazersail > Minicate > Pariza > Kataribhog > Kalijira. DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11514 Dhaka Univ. J. Biol. Sci. 21(2): 163-168, 2012 (July)